Three-Dimensional Observations of an Aperiodic Oscillatory Gliding Behavior in Myxococcus xanthus Using Confocal Interference Reflection Microscopy - Liam M. Rooney (American Society for Microbiology, 2020)
ABSTRACT The deltaproteobacterium Myxococcus xanthus is a model for bacterial motility and has provided unprecedented insights into bacterial swarming behaviors. Fluorescence microscopy techniques have been invaluable in defining the mechanisms that are involved in gliding motility, but these have almost entirely been limited to two-dimensional (2D) studies, and there is currently no understanding of gliding motility in a three-dimensional (3D) context. We present here the first use of confocal interference reflection microscopy (IRM) to study gliding bacteria, revealing aperiodic oscillatory behavior with changes in the position of the basal membrane relative to the substrate on the order of 90 nm in vitro. First, we use a model planoconvex lens specimen to show how topological information can be obtained from the wavelength-dependent interference pattern in IRM. We then use IRM to observe gliding M. xanthus bacteria and show that cells undergo previously unobserved changes in their adhesion profile as they glide. We compare the wild type with mutants that have reduced motility, which also exhibit the same changes in the adhesion profile during gliding. We find that the general gliding behavior is independent of the proton motive force-generating complex AglRQS and suggest that the novel behavior that we present here may be a result of recoil and force transmission along the length of the cell body following firing of the type IV pili. IMPORTANCE 3D imaging of live bacteria with optical microscopy techniques is a challenge due to the small size of bacterial cells, meaning that previous studies have been limited to observing motility behavior in 2D. We introduce the application of confocal multiwavelength interference reflection microscopy to bacteria, which enables visualization of 3D motility behaviors in a single 2D image. Using the model organism Myxococcus xanthus, we identified novel motility behaviors that are not explained by current motility models, where gliding bacteria exhibit aperiodic changes in their adhesion to an underlying solid surface. We concluded that the 3D behavior was not linked to canonical motility mechanisms and that IRM could be applied to study a range of microbiological specimens with minimal adaptation to a commercial microscope.